1992
DOI: 10.1111/j.1349-7006.1992.tb00132.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel Complications with HTLV‐1‐associated Myelopathy/Tropical Spastic Paraparesis: Interstitial Cystitis and Persistent Prostatitis

Abstract: Lower urinary symptoms associated with HTLV‐1‐associated myelopathy/tropical spastic paraparesis (HAM/TSF) are common, but have been regarded as ‘neurogenic’ due to spinal involvements. However, in some cases, these symptoms are persistent, progressive, and not directly correlated with the severity of other neurologic symptoms of the lower spinal cord. These findings prompted us to locate organic lesions in the lower urinary tract and to correlate them with HTLV‐1 infection. Among 35 HAM patients with lower ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Only a small proportion ( < 5%) of HTLV-I-infected individuals will develop HAM/TSP or other organ disorders [4][5][6][7][8][9][10][11], while more than 95% will remain asymptomatic for life [12]. The role of HTLV-I in these diseases remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Only a small proportion ( < 5%) of HTLV-I-infected individuals will develop HAM/TSP or other organ disorders [4][5][6][7][8][9][10][11], while more than 95% will remain asymptomatic for life [12]. The role of HTLV-I in these diseases remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…27 The possible HTLV-I1 HAM case had subepithelial lymphocytic nodules in the bladder without evidence of neurogenic contractions. Nomata et al 33 suggested that infiltration of the bladder with HTLV-I infected lymphocytes may be responsible for bladder symptoms in at least a minority of HAM patients. This case would suggest that HTLV-I1 may cause a similar clinical syndrome.…”
mentioning
confidence: 99%
“…Conversely, bladder and bowels symptoms such as frequency and constipation are common in both HAM and pregnancy whilst gait can be expected to worsen due to the physiological changes in pregnancy. Neurogenic bladder which is commonly observed in HAM/TSP (Araujo, 2015), could impact urinary infection rate (Nomata et al, 1992), which, in turn, can induce preterm birth (Dautt-Leyva et al, 2018).…”
Section: Htlv-1 Infection In Pregnant Womenmentioning
confidence: 99%